Security interventions for workplace violence in the emergency department. (25th June 2018) - Mitra, Biswadev; Nikathil, Shradha; Gocentas, Robert; Symons, Evan; O'Reilly, Gerard; Olaussen, Alexander
Abstract: Objectives: Despite a policy of zero tolerance towards workplace violence (WPV) in Australian public hospital EDs, the incidence of WPV continues to increase. The aim of this study was to characterise security responses to WPV within an adult level 4 ED. Methods: A retrospective single‐centre review of episodes of WPV perpetrated by adults occurring within the ED was conducted between 1 January 2013 and 31 December 2015. Cases were identified using a prospectively recorded security register that records all events of security personnel attendance. The presence of police officers on initial presentation was the primary exposure variable. Results: There were 1853 violent episodes committed by 1224 patients requiring security intervention during the study period, with half the episodes ( n = 916; 49%) involving perpetrators who had committed at least two or more violent acts during the study period. Most cases ( n = 1057, 57%; 95% CI: 55–59) occurred in the absence of police presence. Only 144 (7.8%) cases were managed by the presence of security personnel without physical security interventions. Conclusions: EDs should not rely on police response to prevent or handle violence. The finding of a high proportion of events being perpetrated by repeat offenders indicate that data sharing between EDs for identification of perpetrators of WPV can be useful for prevention of future episodes. ACEM policy for WPV in EDs should encompass further details on security credentialing and preventive strategies towards minimisation of WPV in the Australian EDs.